An Investigation of the Impact of Inquiry-Based Learning in Mathematics on the Students’ Perceptions of the Learning Environment and Attitudes Towards Mathematics in some Abu Dhabi Schools - Robinson, Jennifer Maree (Curtin University, 2020)
This study, carried out in four schools in the UAE, compared students in classes of mathematics teachers exemplary in the use of explorations with those who were not (learning environment perceptions and attitudes). Data collection involved surveys (n=291 students), lesson observations and focus-group interviews (n=27 students). Students taught by teachers exemplary in the use of explorations reported statistically significantly (p<.01) more favourable learning environment perceptions and attitudes than their counterparts who were not.